Papers on the 1962 election : fifteen papers on the Canadian general election of 1962 - Meisel, John (Toronto : University of Toronto Press, 1964)
The essays included in this volume do not follow any one theme, nor are they given unity by a shared frame of reference. Each author dealt with some aspect of the 1962 election without any concern with what was being attempted by the others.
The Press of Ontario and the Election by T.H. Qualter and K.A. MacKirdyThe Counter-Revolution in Saskatchewan, by Norman Ward; The NDP: British Columbia's Labour Party, by Walter D. Young; PART THREE: NATIONAL STUDIES; The Social Bases of Political Cleavage in 1962, by Robert L. Alford; Group Perceptions and the Vote: Some Avenues of Opinion Formation in the 1962 Campaign, by S. Peter Regenstreif; Political Behaviour and Ethnic Origin, by Mildred A. Schwartz; Conclusion: An Analysis of the National Results, by John Meisel
Fifteen papers on the Canadian general election of 1962.
Mimeographed.
Reprinted in 2018.
Online resource; title from PDF title page (EBSCO, April 11, 2019).
Print version record.
JSTOR
Keywords: Canada. -- Parliament -- Elections; Canada. -- Parliament; Elections -- Canada; Élections -- Canada; POLITICAL SCIENCE -- Political Process -- Elections; POLITICAL SCIENCE -- Political Process -- General; Elections; Political science; Canada